Frequent Mutations of VHL Gene and the Clinical Phenotypes in the Largest Chinese Cohort With Von Hippel–Lindau Disease - Hong, Baoan; Ma, Kaifang; Zhou, Jingcheng; Zhang, Jiufeng; Wang, Jiangyi; Liu, Shengjie; Zhang, Zhongyuan; Cai, Lin; Zhang, Ning; Gong, Kan (Frontiers in Genetics, 2019)
Von Hippel–Lindau (VHL) disease is a rare autosomal-dominant inherited tumor syndrome. We aimed to analyze the correlations between frequent VHL mutations and phenotypes in Chinese VHL families. We screened 540 patients from 187 unrelated Chinese VHL families for 19 frequent VHL mutations. The penetrance and mean age of onset for VHL-associated susceptible organs were calculated and compared. The overall survival of VHL patients was described with Kaplan-Meier curves. Among the 19 frequent germline mutations, there were four hot-spot mutation sites (194, 481, 499 and 500). Missense mutations were the most common types of mutations (70.0%) followed by nonsense mutations (20.0%) and splicing mutations (10.0%). Due to the diversity of these mutations, the penetrance for each organ and the age of onset are distinct. Even in cases of similar mutations, variance in the penetrance and age of onset was observed. The mean age at death for the patients in this cohort was 42.4±13.5 years, and variability was observed in the Kaplan-Meier curves. We present a precise summary of the phenotypes for the frequent VHL mutations in the largest Chinese VHL cohort, which provide valuable strategies for genetic counseling and clinical surveillance of VHL individuals.